Can Trainings on Women's Voice and Agency Raise Women's Aspirations, Entrepreneurial Activities, and Well-being? Evidence From Rural Nigeria - Kosec, Katrina; Kyle, Jordan; Mo, Cecilia (AEA RCT Registry, 2023)
Do training interventions designed to strengthen women’s individual and collective efficacy and political participation influence their economic behaviors and outcomes--specifically, their aspirations, entrepreneurial activities, and well-being? What, if any, additive effects do training interventions intended to improve husbands' allyship in women's empowerment and gender equality play? We will answer these questions with a randomized control trial to be implemented in 450 communities (i.e., wards) across three southwestern states of Nigeria (Ogun, Osun, and Oyo) in 2023. In both treatment and control communities, we will recruit previously unaffiliated women to join women’s action committees (WACs) to be trained by ActionAid Nigeria: 1/3 of WACs (control group) will receive basic training in civic education; 1/3 (treatment group 1) will receive civic education training in addition to intensive training in advocacy, leadership, and organizing; and 1/3 (treatment group 2) will receive the same trainings as treatment group 1 and their husbands will be invited to participate in a parallel men's training focused on men's allyship in women's empowerment and gender equality. In addition to their effects on economic behaviors and outcomes, we will also examine potential mechanisms explaining these effects, by considering the effects of treatment on measures of women's beliefs in self- and group efficacy; women's locus of control; women's self-esteem; women's trust levels; women's perceptions of the cause of poverty; women’s own gender norms about views on appropriate roles for women; and intra-household bargaining power between husbands and wives over economic decision-making. If we secure additional funding, we will also assess whether husbands’ gender norms about appropriate roles for women; husbands’ supportive actions to facilitate women’s activities outside the home; husband's beliefs that supporting women's participation is socially normative; and recognition that men have an important role to play in supporting women's participation are mechanisms.